DAYA TARIK WISATA ROHANI GUA KEREP AMBARAWA - Atmoko, T. Prasetyo Hadi (Sekolah Tinggi Pariwisata AMPTA, 2016)
Central Jawa Province obviously one of tourist destinations in Indonesia either nature or historical and cultural attractions. The existence of Mary Cave Kerep Ambarawa also contribute to tourism in Central Jawa as attraction of spiritual tourism. The objectives of this research are to acknowledge how to access to the location of Mary Cave Kerep Ambarawa as well as to recognize how are the facilities that support Mary Cave Kerep Ambarawa. The methods of research being used are observation, interview and books study. Mary Cave Kerep Ambarawa is resided in Jl. Tentara Pelajar, Dusun Kerep, Panjang Sub-district, Ambarawa District, Semarang Regency, Central Jawa Province. Geographically Mary Cave Kerep Ambarawa is located in south slope hill of Ungaran mountain. The attraction of Mary Cave Kerep Ambarawa appeals from its Mary Cave views. It is the highest Mother Mary statue in the world and its inscriptions. Mary Cave Kerep Ambarawa is shaped in artificial cave with stack stone bonded with cement, sand and lime. The cave overlooks to the east and is shaded by tall tree and lush. From one of the cave there is a statue of Mother Mary Lourdes style without a crown. Viewed from the access, to object of religious tourism in Mary Cave Kerep with an area around 5 hectares or more is not stiff. When leaving from the city of Semarang the visitor can be able to grab a Yogyakarta line bus. Vice versa, when leaving from Yogyakarta select bus to Semarang, down to Ambarawa terminal. Similarly, when using personal vehicle travel to Semarang- Yogyakarta route, arrive at Ambarawa terminal bus, there is a signposts for the entrance to the tourist attraction, which is the entrance to the west and down to the ramp about 1 KM. The facilities are provided in Mary Cave Kerep Ambarawa specifically: hall, transit building, and prayer room, parking lot, shops object spiritual, church, food stalls around the area of the Cave, and accommodation, such as hotels and homestay. Keywords: Attraction, Spiritual Tourism, Mary Cave